Expression of Glycolysis-Related Proteins in Cancer of Unknown Primary Origin - Bonatelli, Murilo; Fornari, Isabella Fernandes; Bernécule, Priscila Neves; Pinheiro, Lara Esquiapatti; Costa, Ricardo Filipe Alves; Longatto-Filho, Adhemar; Junior, João Neif Antonio; Silva, Eduardo Caetano Albino; Cárcano, Flávio Mavignier; Pinheiro, Céline (Frontiers in Oncology, 2021)
Introduction Cancer of unknown primary origin (CUP) is defined as metastatic cancer without identification of the primary site. Considering that only 15–20% of patients with CUP show a favorable outcome, identifying biomarkers may help improve the clinical management of patients who do not respond well to conventional therapies. In this context, the study of the metabolic profile of CUP may pave the way to establish new biomarkers and/or therapeutic targets; therefore, this study aimed to characterize the expression of metabolism-related proteins in CUP. Materials and Methods The expression of monocarboxylate transporters MCT1, MCT2 and MCT4, their chaperone CD147, the glucose transporter GLUT1 and the pH regulator CAIX was evaluated by immunohistochemistry in a series of 118 CUP patients, and the results were associated with the available clinicopathological information. Results The metabolism-related proteins MCT1, MCT4, CD147, GLUT1 and CAIX were expressed in a critical portion of the CUP (approximately 20 to 70%). MCT1 and CD147 were both more frequently expressed in cases with lymph nodes as metastasis dominant sites (p = 0.001) as well as in samples from lymph nodes (p <0.001 and p = 0.002, respectively), while MCT1 expression was more frequently expressed in squamous cell carcinomas (p = 0.045). A higher overall survival was observed in patients with tumors positive for GLUT1 and CAIX expression (p = 0.011 and p = 0.041, respectively), but none of the proteins was an independent prognostic factor for overall survival in multivariable analysis. Conclusion The results suggest that a portion of CUPs present a hyperglycolytic phenotype, which is associated with higher overall survival.